The true loss caused by biodiversity offsets. (December 2015) - Moreno-Mateos, David; Maris, Virginie; Béchet, Arnaud; Curran, Michael
Abstract: Biodiversity offsets aim to achieve a "no-net-loss" of biodiversity, ecosystem functions and services due to development. The "no-net-less" objective assumes that the multi-dimensional values of biodiversity in complex ecosystems can be isolated from their spatial, evolutionary, historical, social, and moral context. We examine the irreplaceability of ecosystems, the limits of restoration, and the environmental values that claim to be compensated through ecosystem restoration. We discuss multiple ecological, instrumental, and non-instrumental values of ecosystems that should be considered in offsetting calculations. Considering this range of values, we summarize the multiple ecological, regulatory, and ethical losses that are often dismissed when evaluating offsets and the "no-net-loss" objective. Given the risks that biodiversity offsets pose in bypassing strict regulations, eroding our moral responsibility to protect nature, and embracing misplaced technological optimism relating to ecosystem restoration, we argue that offsets cannot fulfil their promise to resolve the trade-off between development and conservation. If compensation for biodiversity loss is unavoidable, as it may well be, these losses must be made transparent and adequate reparation must embrace socio-ecological uncertainty, for example through a Multi-Criteria Evaluation framework. Above all, strict protection legislation should be strengthened rather than watered down as is the current trend.